2000
DOI: 10.1042/0264-6021:3520491
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase D in rat myometrium: occurrence of a membrane-bound ARF6 (ADP-ribosylation factor 6)-regulated activity controlled by βγ subunits of heterotrimeric G-proteins

Abstract: Both protein kinase C and protein tyrosine kinases have been shown to be involved in phospholipase D (PLD) activation in intact rat myometrium [Le Stunff, Dokhac and Harbon (2000) J. Pharmacol. Exp. Ther. 292, 629-637]. In this study we assessed the involvement of monomeric G-proteins in PLD activation in a cell-free system derived from myometrial tissue. Both the PLD1 and PLD2 isoforms were detected. Two forms of PLD activity, essentially membrane-bound, were found in myometrial preparations. One form was sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…Synthetic peptides corresponding to the N terminus of the ARFs inhibit such ARF activities as intra-Golgi transport, the accumulation of coated vesicles and buds from Golgi preparations, phospholipase D (PLD) activation, and catecholamine secretion (30,(43)(44)(45)(46). We have shown that a pool of ␤arrestin1 is docked at the plasma membrane at a site distinct from the LH/CG receptor and that, upon LH/CG receptor activation, ␤arrestin1 binds to the LH/CG receptor resulting in an uncoupling of receptor and G s (1-3).…”
Section: Resultsmentioning
confidence: 99%
“…Synthetic peptides corresponding to the N terminus of the ARFs inhibit such ARF activities as intra-Golgi transport, the accumulation of coated vesicles and buds from Golgi preparations, phospholipase D (PLD) activation, and catecholamine secretion (30,(43)(44)(45)(46). We have shown that a pool of ␤arrestin1 is docked at the plasma membrane at a site distinct from the LH/CG receptor and that, upon LH/CG receptor activation, ␤arrestin1 binds to the LH/CG receptor resulting in an uncoupling of receptor and G s (1-3).…”
Section: Resultsmentioning
confidence: 99%
“…Possible pathways connecting the Ras superfamily GTPases and phospholipases have been reported. The GTPases RhoA and Arf 6 ( Table 1D ) are direct activators of PLD 2 ( 39, 40 ) from rat or human origin ( 41 ).…”
Section: Methodsmentioning
confidence: 99%
“…Both ARF1 and ARF6 have been implicated in PLD activation in phagocytic cells. 13,14 Sphingolipid signaling is involved in cell growth, differentiation, and apoptosis. 15 During PMN phagocytosis, plasma membraneassociated neutral sphingomyelinase is activated, resulting in accumulation of ceramide within the cell.…”
Section: Introductionmentioning
confidence: 99%